2004
DOI: 10.1002/ejic.200400033
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of CH3NH2 and (CH3)2NH by NiIII(cyclam)(H2O)23+ in Aqueous Solutions

Abstract: NiII (1,4,8,11-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The formation of Ni II L -2H 2+ requires the formation of a C-N double bond, i. e. a significant change in geometry, which is facilitated by the less rigid open ligand. [14] This conclusion is in agreement with the observation that the stabilities of the isomers of Ni III (5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraaazacyclotetradecane) differ considerably. [15] …”
Section: Oxidation Of the Complex By Br 2 ·-Ion Radicalssupporting
confidence: 88%
“…The formation of Ni II L -2H 2+ requires the formation of a C-N double bond, i. e. a significant change in geometry, which is facilitated by the less rigid open ligand. [14] This conclusion is in agreement with the observation that the stabilities of the isomers of Ni III (5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraaazacyclotetradecane) differ considerably. [15] …”
Section: Oxidation Of the Complex By Br 2 ·-Ion Radicalssupporting
confidence: 88%
“…The results are similar to the electro-oxidation of these amines on glassy carbon electrodes in the presence of NiL 2+ in solution. [18] Thus, the results demonstrate that NiL 2+ acts as an electrocatalyst also when it is immobilized in sol-gel matrices.…”
Section: Oxidation Of Aminesmentioning
confidence: 92%
“…This choice is based on the following arguments: (1) NiL 2+ is a known electrocatalyst for the oxidation of amines in aqueous solutions [18] and in heterogeneous systems. [19] (2) These amines are formed in a variety of industrial processes as byproducts, [20] that is, as pollutants, and therefore their oxidation is of environmental interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently it was shown that Ni(III)(cyclam), Ni III L, oxidizes methyl amine via [14]: [14].) The suggestion that I is a key intermediate in the process prompted us to check whether I, a radical, reacts with NO, a radical, a reaction which will result in the reductive nitrosation of CH 3 NH 2 .…”
mentioning
confidence: 99%